Rapid Compound Integrity Assessment for High-Throughput Screening Hit Triaging. (February 2021) - Shou, Wilson Z.; Gerritz, Samuel W.; Harden, David; Lawrence, R. Michael; Chase, Peter; Chin, Jefferson; Surti, Neha; Lippy, Jonathan S.; Weller, Harold N.; Nielsen, Julia; Weerakoon, Darshani
Hits from high-throughput screening (HTS) assays are typically evaluated using cheminformatics and/or empirical approaches before a decision for follow-up (activity confirmation and/or sample resynthesis) is made. However, the compound integrity (i.e., identity and purity) of these hits often remains largely unknown at this stage, since many compounds in the screening collection could undergo various changes such as degradation, polymerization, and precipitation during storage over time. When compound integrity is actually assessed for HTS hits postassay to address this issue, the process often increases the overall cycle time by weeks due to the reacquisition of the samples and the lengthy liquid chromatography–ultraviolet/mass spectrometric analysis time. Here we present a novel approach where compound integrity data are collected concurrently with the concentration–response curve (CRC) stage of HTS, with both assays occurring either in parallel on two distributions from the same liquid sample or serially using the original source liquid sample. The rapid generation of compound integrity data has been enabled by a high-speed ultra-high-pressure liquid chromatography–ultraviolet/mass spectrometric platform capable of analyzing 2000 samples per instrument per week. From this parallel approach, both compound integrity and CRC potency results for screening hits become available to medicinal chemists at the same time, which has greatly enhanced the decision-making process for hit follow-up and progression. In addition, the compound integrity results from recent hits provide a real-time and representative "snapshot" of the sample integrity of the entire compound collection, and the data can be used for in-depth analyses of the screening collection.